ARCHITECTURE AND FUNCTIONALITY OF THE PROGRAMM COMPLEX "KSU FEEDBACK" (Journal of Information Technologies in Education (ITE), 2010)
The problem of building of the feedback is reviewed in this article. The version of its solving with help of program complex "KSU Feedback" is given. The architecture and interface of this project is analyzed in details. The advantages of service are stressed as compared with exiting solutions.
Keywords: architecture; database; educational process; feedback; interrogation; monitoring survey; software